Pengembangan Media Pembelajaran Power Point Subtema Keberagaman Budaya Bangsaku Kelas IV MI/SD - Diah Rizki Nur Kalifah; Andi Prastowo (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2021)
In learning teachers have used Powerpoint media but still lacking in learning design and often teachers use image media in learning. The purpose of this study is Powerpoint media design. The method used is R&D (Research and Development) adopted from Borg and Gall by combining assure models. The results of this study obtained two validators namely validator A is 3.52 out of 4 while validator B is 3.59 out of 4, has